2006
DOI: 10.1590/s0100-83582006000200018
|View full text |Cite
|
Sign up to set email alerts
|

Control de lecheron (Euphorbia dentata) con glifosato

Abstract: RESUMEN -Euphorbia dentata es una maleza anual, de ciclo primaveral -estival que está presente en el 85% del área agrícola del partido de Azul, provincia de Buenos Aires, Argentina. Estudios en campo fueron conducidos durante dos años a fin de realizar ajustes de dosis y momentos de aplicación que permitan lograr una alta eficacia de control de E. dentata con glifosato y estudiar el uso de distintas concentraciones de un surfactante, para lograr resultados más predecibles en aplicaciones a campo. Se realizó un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Moreover, by increasing doses of glyphosate at 356 or 712 g ha -1 in all periods of evaluation, controls of I. unisetus were statistically similar, regardless of pH of water application ( In this experiment, again determined that glyphosate is the most important factor to control I. unisetus, and that increasing the dose there is a more efficient control of this weed. This coincides with that reported by other authors for different weed species (Faccini and Puricelli, 2002;Koger et al, 2004;Juan et al, 2006;Pinto et al, 2009). …”
Section: Experimento 2: Dosis De Glifosato Y Ph Del Agua De Aplicaciónsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, by increasing doses of glyphosate at 356 or 712 g ha -1 in all periods of evaluation, controls of I. unisetus were statistically similar, regardless of pH of water application ( In this experiment, again determined that glyphosate is the most important factor to control I. unisetus, and that increasing the dose there is a more efficient control of this weed. This coincides with that reported by other authors for different weed species (Faccini and Puricelli, 2002;Koger et al, 2004;Juan et al, 2006;Pinto et al, 2009). …”
Section: Experimento 2: Dosis De Glifosato Y Ph Del Agua De Aplicaciónsupporting
confidence: 93%
“…Lo anterior coincide por lo reportado por otros autores para diferentes especies de malezas (Faccini y Puricelli, 2002;Koger et al, 2004;Juan et al, 2006;Pinto et al, 2009).…”
Section: Experimento 2: Dosis De Glifosato Y Ph Del Agua De Aplicaciónunclassified
“…Studies conducted in the late 1990s, on agricultural lots in the central area of Buenos Aires Province, reported weed densities rates between 20 and 200 plants m -2 (Juan et al, 1996), where as some recent researches revealed an increase in population density, ranging from 300 to 900 plants m -2 (Juan et al, 2011;Núñez Fré et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…It is an spring-summer annual weed that causes significant yield reduction in soybean in central and southeastern sections of Buenos Aires Province, Argentina (Juan et al, 2011). In the last two decades it has been observed an increase in constancy, density and geographical distribution of E. davidii in this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation